Quality of red mombin fruits (Spondia purpurea L.) subjected to mechanical damage (Research, Society and Development, 2025)
The labor shortage in the cultivation of rubber trees is a problem for the economic development of the crop. Harvesting mechanization can boost cultivation. However, for a machine design, it is necessary to know the resistance of the fruit to mechanical damage. The objective of this study was to investigate the feasibility of mechanized harvesting by evaluating the effect of mechanical damage applied to the fruits in the laboratory and the fruit detachment force evaluated in the field. A sample of fruits was released in free fall, at heights of 1.0 and 1.3 meters, onto three surfaces (bubble wrap, ceramic floor (without protection) and air cushion). These samples were then stored at room conditions and analyzed periodically for 5 days. The following parameters were evaluated: longitudinal and transverse diameters, loss of fresh mass, mechanical damage, incidence of rot and fruit detachment force. Analysis of variance (ANOVA) was performed, followed by the Tukey test to compare the means of fresh mass loss. The results demonstrated that the bubble wrap and air cushion surfaces reduced the damage caused by impacts. It was observed that the detachment force decreased with the increase in the ripening stage. The results demonstrated that the seriguela fruit subjected to mechanical damage presented a low incidence of rot and good quality maintenance, presenting promising characteristics for mechanical harvesting.